Intracranial Aneurysms Induced by RUNX1 Through Regulation of NFKB1 in Patients With Hypertension-An Integrated Analysis Based on Multiple Datasets and Algorithms - Li, Yang; Zhang, Zhen; Liu, Donghua (Frontiers in Neurology, 2022)
Objective: Single-cell analysis can be performed to investigate the mechanisms for intracranial aneurysm (IA) caused by monocytes/macrophages in the hypertensive microenvironment. This study aimed to investigate the hub genes contributing to AI progression in patients with hypertension and to identify potential therapeutic targets. Methods: The bulk RNA sequencing (RNA-seq) datasets of hypertension and IA were downloaded from the Gene Expression Omnibus (www.ncbi.nlm.nih.gov/geo) database. Next, they were used to calculate disease-related differentially expressed genes (DEGs) at the individual level. A single-cell RNA-seq dataset of patients with abdominal aortic aneurysms was used to analyze monocyte/macrophage-related DEGs. Based on the monocyte/macrophage-related DEG data, a protein-protein interaction (PPI) network was established. Further, a core sub-network and hub genes were identified from this PPI network. Finally, the key genes were validated in an independent clinical cohort. Results: In total, 2550 and 3079 DEGs were identified separately from the bulk RNA-seq datasets of hypertension and IA, respectively. Using combined monocyte/macrophage-related DEGs from abdominal aortic aneurysm, five hub DEGs, including IFI30, SERPINE1, HMOX1, IL24, and RUNX1, were detected. Moreover, 57 genes were found in the IA bulk RNA-seq dataset. To construct a predictive model for the risk of IA, the Support Vector Machines–Recursive Feature Elimination algorithm was applied to further screen 7 (RPS4Y1, DDX3Y, RUNX1, CLEC10A, PLAC8, SLA, and LILRB3) of 57 genes. RUNX1 was the hub gene that regulated NFKB1 in the monocyte/macrophage-related PPI network. Gene-set enrichment analysis revealed that RUNX1 played a role in IA progression by regulating hematopoietic stem cell differentiation and abnormal platelet production. Conclusion: Single-cell analysis using clinical data showed that RUNX1 in monocytes/macrophages was associated with a higher risk of IA via the regulation of NFKB1 among patients with hypertension.